Characterization and Technological Features of Autochthonous Coagulase-Negative Staphylococci as Potential Starters for Portuguese Dry Fermented Sausages - Semedo-Lemsaddek, Teresa (2017)
The manufacture of dry fermented sausages is an important part of the meat industry in Southern Europeancountries. These products are usually produced in small shops from a mixture of pork, fat, salt, and condiments andare stuffed into natural casings. Meat sausages are slowly cured through spontaneous fermentation by autochthonousmicrobiota present in the raw materials or introduced during manufacturing. The aim of this work was to evaluate thetechnological and safety features of coagulase-negative staphylococci (CNS) isolated from Portuguese dry fermented meatsausages in order to select autochthonous starters. Isolates (n = 104) obtained from 2 small manufacturers were identiﬁedas Staphylococcus xylosus, Staphylococcus equorum, Staphylococcus saprophyticus,andStaphylococcus carnosus. Genomically diverseisolates (n = 82) were selected for further analysis to determine the ability to produce enzymes (for example, nitrate-reductases, proteases, lipases) and antibiotic susceptibility. Autochthonous CNS producing a wide range of enzymes andshowing low antibioresistance were selected as potential starters for future use in the production of dry fermented meatsausages.